Seed Quality Attributes in Bitter Gourd (Momordica charantia L.) - S. K. SINGH; HARI HAR RAM (Seed Research, 2026)
Thirty-six genotypes (eight parental lines and 28 F, hybrids) of bitter gourd were subjected to seed quality assessment under laboratory conditions utilizing standard germination test. The genotypic differences were highly significant in both the seasons for number of seeds per fruit, seed yield/fruit and seed vigour index. The genotypic difference for seed germination was highly significant only in the rainy season experiment.